CAUGHT IN THE SCROLL: WHEN FOMO, SOCIAL MEDIA ADDICTION, AND SOCIAL ANXIETY LEAD TO IMPULSIVE BUYING AND POST PURCHASE REGRET AMONG GEN Z - Dhiky Hardianto; Panca Kurniati; Muhammad Arifiyanto (Universitas PGRI Semarang, 2025)
This study examines digital anxiety in the era of technology and social media, which causes consumer confusion in purchasing decisions, especially among Generation Z (born 1997-2012) in Indonesia. This generation is susceptible to Fear of Missing Out (FOMO), social media addiction (consisting of weak behavioral control and dysfunctional behavior), and social anxiety, which can trigger impulsive buying and post-purchase regret. The main objective is to analyze the influence of FOMO, social media addiction, and social anxiety on impulsive buying and the influence of impulsive buying on post-purchase regret. The method uses a quantitative approach with Structural Equation Modeling (SEM) based on Partial Least Square (PLS) version 3.0, involving a minimum of 209 Generation Z respondents who are active on social media and have shopped online through purposive sampling in Indonesia. The results show that FOMO, weak behavioral control, and dysfunctional behavior have a significant positive effect on impulsive buying, while social anxiety is not significant. Impulsive buying also has a significant positive effect on post-purchase regret. The implications of the research include understanding the negative impacts of social media on consumer well-being, as well as recommendations for digital platforms and governments to create regulations and awareness campaigns to prevent regret in Generation Z.